Eating with our ears: assessing the importance of the sounds of consumption on our perception and enjoyment of multisensory flavour experiences - Spence, C (BioMed Central, 2015)
Sound is the forgotten flavour sense. You can tell a lot about the texture of a food—think crispy, crunchy, and crackly—from the mastication sounds heard while biting and chewing. The latest techniques from the field of cognitive neuroscience are revolutionizing our understanding of just how important what we hear is to our experience and enjoyment of food and drink. A growing body of research now shows that by synchronizing eating sounds with the act of consumption, one can change a person’s experience of what they think that they are eating.